IMPLEMENTASI GAYA KEPEMIMPINAN MENGGUNAKAN TIPE PATERNALISTIK DALAM MENINGKATKAN SUMBER DAYA MANUSIA - Melisa Srimurty Aprilia; Intan Alvionita; Misbahul Khoiri; Moch. Fanil Abrori; Yunita Amalia (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2021)
This study aims to support and study the role of leaders in improving Desa Bremi in social psychology. The style or style of a leader greatly influences his followers or subordinates. The type or style of a paternalistic leader is a leader who uses or applies to perceptions, values ​​held, attitudes and protections seen in needs. Desa bremi is a village located in District Krucil of Probolinggo Regency, East Java, which is expected to be able to provide quality human resources. As a leader in the village Bremi made efforts to be able to direct HR well from the problem of HR development. This study used a qualitative descriptive study using a sample technique of 4 respondents using interviews and observation and documentation. From this sample the researchers chose from the village apparatus, one RT / RW chairman and 2 villagers.